Solid-state morphology, structure, and tensile properties of polyethylene/polyamide/nanoclay blends: Effect of clay fraction. (April 2017) - Huitric, Jacques; Ville, Julien; Mederic, Pascal; Aubry, Thierry
Abstract: The effect of nanoclay fraction on the linear and non-linear tensile properties of a polyethylene/polyamide 12 blend with droplet morphology was investigated. All ternary blends were prepared at a fixed polyamide (PA) weight fraction of 20%, and at clay volume fractions varying from 0.5 to 2.5% relative to PA. Scanning electron microscopy and transmission electron microscopy were used to characterize the morphology of the blends and the clay interphase structure. The nanoclay content was shown to strongly influence both linear and non-linear tensile properties. Young's modulus, elongation at yield, yield strength, tensile strength and elongation at break as a function of clay fraction were studied and discussed in terms of morphological changes and strain-induced structural reorganization of the clay interphase.